Characteristics of Sambung Nyawa (Gynura procumbens) mix with Cinnamon (Cinnamomum burmannii) as Functional Drink Instant Powder - Ulsiani, Della; Yenrina, Rina; Azima, Fauzan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Instant powder drinks are practical, water-soluble beverage products with a long shelf life. This study developed a functional instant powder drink from sambung nyawa (Gynura procumbens) leaf extract, enriched with cinnamon bark extract to enhance flavor and antioxidant properties. The goal was to see how different amounts of cinnamon bark powder (0%, 15%, 20%, 25%, and 30%) affected the physical, microbial, and taste qualities of the final drink and to find the best recipe. A completely randomized design with three replications was used. We analyzed the data using ANOVA and DNMRT at a 5% significance level. Results showed that cinnamon addition significantly affected total polyphenols, antioxidant activity (IC50), titratable acidity, dissolving time, taste, and aroma, but had no significant effect on moisture content, ash content, water-insoluble fraction, total plate count, or color. The best mix included 30% cinnamon, which resulted in 2.11% moisture, 0.33% ash, 0.99% total acidity, 201.45 mg GAE/g total polyphenols, 78.75 mg/L IC50, 33.44 seconds to dissolve, 0.93% insoluble part, 2.37×10³ CFU/g total plate count, and good ratings for color (3.7, liked), taste (3.33, neutral), and aroma (3.67, liked). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and Production